O5.1. GREY MATTER BRAIN CHANGES IN MEDICATED AND UNMEDICATED FIRST EPISODE PSYCHOSIS: A RANDOMISED PLACEBO-CONTROLLED TRIAL. (9th April 2019) - Chopra, Sidhant; Fornito, Alex; Francey, Shona; O'Donoghue, Brian; Nelson, Barnaby; Graham, Jessica; Baldwin, Lara; Yuen, Hok Pan; Allott, Kelly; Alvarez-Jimenez, Mario; Pantelis, Christos; Harrigan, Suzy; et al.
Abstract: Background: First episode psychosis (FEP) has been consistently associated with changes within grey matter. No prospective study to date has been able to distinguish the differential effects of antipsychotic medication from the natural progression of psychosis on these changes. Methods: We conducted a triple-blind randomised placebo-control trial where 90 people aged between 15 to 24 with FEP received either an atypical antipsychotic or a placebo pill over a treatment period of 6 months, with a sub-group (N=62) undergoing neuroimaging. Both FEP groups received intensive psychosocial therapy. A healthy control group (n=27) were also recruited. T1-w structural MRI scans at 3-Tesla were taken at baseline, 3-months and 12-months. Longitudinal Voxel-Based-Morphometry was used to identify grey matter areas where the rate of change between the three groups was significantly different across timepoints. Results: Using robust non-parametric methods, and after controlling for baseline age, sex, total intracranial volume and medication dose following treatment conclusion, a cluster within the medial and inferior temporal cortex showed a significant group x time interaction (k = 213, p < 0.05 FWE-corrected). Within the medication group, the volume of this area normalised to that of the healthy control group at the 3-month time point, then continued to increase to a size greater than that of the healthy control group at the 12-month follow-up. Volume remained reduced within the placebo group at the 3-month timepoint but trended towards normalisation at the 12-month timepoint. Additionally, the rate of change between baseline and three months within this cluster was significantly correlated (r = -.53, p < 0.01) with the primary trial outcome measure: The Social an Occupational Functional Assessment Scale. Discussion: Antipsychotic medication normalises the initially reduced volume of the temporal cortex. However, a similar pattern of normalization may be seen over a longer period of time in those who received placebo. Additionally, greater change within the same area is associated with poorer functional outcome, suggesting that the processes and networks supported medial and inferior temporal cortex may play a primary role in maintaining social and occupational functioning.